Evolution of Intracerebral Hemorrhage after Intravenous Tpa: Reversal of Harmful Effects with Mast Cell Stabilization. Issue 1 (January 2014) - Marinkovic, Ivan; Mattila, Olli S; Strbian, Daniel; Meretoja, Atte; Shekhar, Shashank; Saksi, Jani; Abo-Ramadan, Usama; Rantanen, Ville; Lindsberg, Perttu J; Tatlisumak, Turgut
Thrombolysis with tissue plasminogen activator (tPA) traditionally demands baseline imaging to rule out intracerebral hemorrhage (ICH), which causes delays in treatment. Preventing possible adverse effects of tPA on ICH would allow rapid on-site thrombolysis in patients with presumed acute ischemic stroke, reducing onset-to-treatment times. We examined how intravenous tPA alters ICH evolution during an extended follow-up, and how mast cell stabilization affects this process. Intracerebral hemorrhage was induced in rats by collagenase injection. Rats received either saline ( n =10), tPA ( n =13), tPA+low-dose cromoglycate ( n =10), or tPA+high-dose cromoglycate ( n =10). Magnetic resonance imaging was performed at 24, 48, and 72 hours after ICH induction, together with neurologic evaluations. During 72 hours of follow-up, tPA administration did not significantly increase hematoma volume (mean±s.d. 83.5±14.3 versus 66.7±14.7  μ L; P =0.256) or hemispheric expansion (14.5±5.0 versus 11.5±5.0%; P =0.457) compared with saline. However, tPA-treated animals had worse neurologic outcomes ( P <0.05), and mortality (8/13 versus 3/10). Combining tPA with high-dose cromoglycate mitigated hemispheric expansion (7.4±1.7 versus 14.5±5.0%; P =0.01), improved neurologic outcome ( P <0.001) and decreased mortality (1/10; P <0.05) compared with t P A alone. Our results suggest tPA increases neurologic deficit in ICH, an effect that was abolished by concomitant mast cell stabilization. Further studies are needed to establish the clinical relevance of these findings.